Translation: to be wordy or not to be / Nur Adila Azira Azmi and Geraldine John Philip De Mello - Azmi, Nur Adila Azira; John Philip De Mello, Geraldine (Akademi Pengajian Bahasa, 2021)
Translation is a transfer process, which aims at the transformation of a written Source Language (SL) text into an optimally equivalent Target Language (TL) text. It requires the syntactic, the semantic and the pragmatic understanding and analytical processing of the Source Language. The objectives of this study are to identify the use of different translation techniques and the usage of words when translating documents of varying lengths and topics. When translating there are few points to consider such as the cultural differences, the regional and dialects differences, the literary aspects and most importantly, to ensure the meaning and context are maintained. Additionally, there are translation techniques which includes the borrowing technique, calque, literal translation and transposition techniques to follow during the translation process. These techniques are used to ensure the meaning, the tone and context of the article are translated accurately from SL to TL. Five documents of varying subjects were translated and from this service, it was found that the words must be translated as simple as they can to ease the intended readers understanding and also not to run away from the contexts of the original document given. A feedback form was given to the participants and the results suggest that the clients were happy with the translated documents.